Analisis Produksi Dan Pemasaran Kakao Di Gampong Tunong Kecamatan Keumala Kabupaten Pidie - Ibrahim Ali (Jurnal Agrisep, 2013)
ABSTRACT. The agricultural sector is a sector that is able to survive in conditions of economic crisis hit Indonesia. This sector plays an important role in the economic recovery in Indonesia, and also became one of the main components of the program and the government's strategy to alleviate kemiskinan.Tujuan Research: To determine Are land, capital and labor influence on produksi.Untuk know cocoa marketing system in the Gampong Tunong Keumala Pidie District. This research purposed survey method. Furthermore, to determine the sample farmers used the technique "Simple Random Sampling". Results: Based on the t-test results obtained tcount t table (3,502 1.33) at the level of 95%, which means that the land is very real effect on the value of farm production of cocoa, and singnifikan rate of 0.004 means that land is very powerful to production (production value) of cocoa. As for the capital obtained tcount ttable (-3.303 1.33) means that the capital does not affect the production of cocoa farming (use of capital in cocoa farming has been exceeded, thus it needs to be deducted), with a rate of 0.005 means that the value singnifikan also very strong capital conjunction with the production (value of production) cocoa farming. whereas for workers obtained tcount ttable (5.042 1.33) at the level of 95%, which means that labor is very significant effect on the value of farm production of cocoa, and singnifikan rate of 0.000 means that labor is very strong influence on the production (production value) of cocoa in the Village Tunong Keumala District of Pidie district. Cocoa marketing system in the Village District of Keumala Kabupetan Tunong efficient Pidie already includes three types of marketing agencies.